Anthropology of language: an introduction to linguistic anthropology - Ottenheimer, Harriet Joseph (Victoria Thomson Wadsworth, 2006)
This text provides an introduction to the field of linguistic anthropology, which appeals to undergraduates from a wide variety of fields and at a wide variety of levels, from freshmen to seniors. This text comes with access to a companion website designed to make the intersection of linguistics and anthropology accessible and interesting to undergraduate students. In addition to THE ANTHROPOLOGY OF LANGUAGE, Harriett Ottenheimer has also creating a workbook/reader that is a perfect bundle option for this text. See the supplement section for details
Bibliography: p 279-286; Glossary: p 263-278